User-Centered UI/UX Design for Intisari Banyumas Souvenir Food E-Commerce Website - Ika Wida Nuragustin; Indy Aurelia Az Zahra; Dill Thafa Jausha (Journal of Software Engineering and Multimedia (JASMED), 2026)
The rapid growth of digital commerce has encouraged local businesses to adopt online platforms to improve accessibility and customer engagement. However, many local souvenir businesses in Indonesia still rely on conventional selling methods and lack user-friendly digital platforms. This study aims to design and evaluate a user-centered e-commerce website for Intisari, a Banyumas souvenir store specializing in traditional products such as gethuk goreng and nopia. The research employed the User-Centered Design (UCD) approach consisting of empathize, define, ideate, prototype, and testing stages. Data collection was conducted through observations, interviews, and questionnaires involving 60 respondents and local UMKM actors to identify user needs and usability expectations. An interactive prototype was developed using Figma by implementing UI/UX principles, Nielsen’s usability heuristics, and Gestalt visual principles. The prototype was evaluated using usability testing scenarios and the System Usability Scale (SUS). The evaluation results showed a task completion rate of 95%, an average checkout completion time of 1 minute and 40 seconds, and a SUS score of 88.33 categorized as “Excellent”. The findings indicate that the implementation of user-centered UI/UX principles significantly improves user satisfaction, usability, and interaction efficiency in local e-commerce platforms. This research contributes to the development of culturally oriented digital commerce platforms that support local UMKM digital transformation and cultural preservation.